Práticas alimentares maternas não nutritivas entre crianças brasileiras : associações com características da mãe e da criança - Ivers, Julia Feltrin [UNIFESP] (2017)
Introduction: The marked increase in the prevalence of overweight and childhood obesity is a worldwide public health problem that affects more diverse ethnicities and socioeconomic groups around the world. In Brazil, there is a clear change in the nutritional profile of children in the last decades, from underweight to overweight, especially in the age group between 5 and 9 years This expressive increase in the rates of childhood obesity is related to environmental changes that lead to a high caloric intake and low energy expenditure. In this obesogenic environment, the strategies used by parents to feed their children represent an important part of the environmental factors that directly affects the formation of eating habits and weight status of the child. The study of feeding practices through which mothers feed their children in order to regulate negative emotions, reward or punish child's behavior is described in the literature as non-nutritive eating practices. In this situation, the foods used are commonly palatable and of high energy density. Some studies on the issue show associations of these parental feeding practices with the development in the child of eating behaviors that leads to the weight gain. Considering that mothers are essentially responsible for child feeding and have an important role in shaping eating habits and child‟s food environment, it is relevant to understand which characteristics of the mother-child dyad are associated with these practices. The aim of this study was to investigate the associations between non-nutritive maternal feeding practices and sociodemographic, anthropometric, dietary and attitudinal characteristics of Brazilian mothers and their children. Methods: This is a cross-sectional observational study conducted with mothers and their two-to-eight-year-old children enrolled in private schools of São Paulo and Campinas, SP, Brazil. Non-nutritive feeding practices used by the mothers were assessed by the “Emotion regulation/Food as reward” factor of the Brazilian version of the Comprehensive Feeding Practices Questionnaire (CFPQ). Sociodemographic, anthropometric, dietary and attitudinal characteristics were self-reported by the mothers. Results: Mothers with lower age and who perceived their child as a little thin or very thin were more prone to feed them with non-nutritive practices. Child‟s characteristics such as preschool age, greater ultra-processed food intake, and overweight or obesity were also found to be associated with increased maternal use of non-nutritive feeding practices. Contrary to our expectations, maternal weight status and child sex were not associated to these feeding practice. Conclusion: The associations in this study allowed us to identify risk groups for non-nutritive feeding practices based on maternal and child characteristics. The results showed that different factors, objective and subjective, may influence the use of non-nutritive feeding practices. Clinical interventions should be done to help mothers to find alternatives to deal with child´s emotions and behaviors other than offering foods.